THEMATIC PROGRESSION IN STUDENTS' EXPLANATORY TEXTS: A Systemic Functional Linguistics Perspective - Sugijarto, - (2010)
This study aims to portray the realisations of Thematic Progression in students' explanatory text. Two research problems are posted; the first one is how students realised Thematic Progression of their explanatory texts. The second research problem relates to the extent to which in terms of thematic progression the students' explanatory texts are consistent with features of scientific texts, i.e. dominant occurence of Simple Linear Progression (SLT) and Constant Thematic Progression (CTP). There were 20 students involved in this study. In analysing the students' texts, this study adopted Halliday's concepts of Theme-Rheme and Danes' Model of Thematic Progression analysis. The study found two primary findings. Firstly, it is found that the students applied four thematic progression patterns, i.e. Simple Linear Progression (SLP), Constant Thematic Progression (CTP), Derived Theme Progression (DTP), and Split Rheme Progression (SRP). Secondly, regarding Thematic Progression distribution, it is found that the students' explanatory texts are consistent with the features of scientific texts. This is suppported by the dominant number of CTP pattern (48.39%) and SLP pattern (32.06%) in those texts. This suggests that the students are able to organise their texts in four thematic organisations. The fact also implies that the students are capable to perform a commonly acceptable organisation of information in scientific texts because their texts are significantly consistent with the features of general English scientific texts in terms of thematic progression, i.e. the dominant realisation of Simple Linear Progression (SLP) and Constant Thematic Progression (CTP)